2003
DOI: 10.1159/000071310
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Somatotropic Axis by Testosterone in Adult Men: Evidence for a Role of Hypothalamic Growth Hormone-Releasing Hormone

Abstract: Testosterone (T) is known to affect the growth hormone (GH) axis. However, the mechanisms underlying the activation of GH secretion by T still remain to be clarified. Available data in animals and humans have shown that withdrawal of somatostatin (SRIH) infusion induces a GH-releasing hormone (GHRH)-mediated rebound release of GH, and there is accumulating evidence that SRIH infusion withdrawal may be a useful test to probe the GHRH function in vivo. With the aim of investigating whether the stimulatory effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 29 publications
1
32
1
Order By: Relevance
“…Similar results were observed in hypogonadal men after 24 wk of T replacement therapy (250 mg im every 3 wk) (5). As a consequence, other studies (5,34) have suggested that the stimulatory action of T may involve promoting GHRH release from the hypothalamus rather than potentiating its action at the level of the pituitary. In addition, T therapy in healthy older men is known to attenuate feedback inhibition by GH and IGF-I (42).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Similar results were observed in hypogonadal men after 24 wk of T replacement therapy (250 mg im every 3 wk) (5). As a consequence, other studies (5,34) have suggested that the stimulatory action of T may involve promoting GHRH release from the hypothalamus rather than potentiating its action at the level of the pituitary. In addition, T therapy in healthy older men is known to attenuate feedback inhibition by GH and IGF-I (42).…”
Section: Discussionsupporting
confidence: 70%
“…However, in healthy older men, high doses of T have been reported not to amplify the maximal stimulatory effect of simultaneous infusion of L-arginine, GHRH, and GH-releasing peptide on GH release (45). Similar results were observed in hypogonadal men after 24 wk of T replacement therapy (250 mg im every 3 wk) (5). As a consequence, other studies (5,34) have suggested that the stimulatory action of T may involve promoting GHRH release from the hypothalamus rather than potentiating its action at the level of the pituitary.…”
Section: Discussionmentioning
confidence: 53%
“…Data from 18 studies in hypogonadal or normal men (n ϭ 149 subjects total) indicate that parenteral T supplementation increases mean GH concentrations by a weighted-mean effect size [standard deviations (SDs)] of 1.8 (7,8,12,17,18,25,30,32,37,39). In women, the effect size of age on GHRH/GHRP-2 stimulation was 1.2 SDs (38).…”
Section: Subjectsmentioning
confidence: 99%
“…Testosterone enhances the secretion of GH [120], an effect mediated at the hypothalamic level by stimulation of GH releasing hormone [121]. Thus, one mechanism how testosterone regulates GH system is through stimulation of GH secretion by testosterone.…”
Section: Testosteronementioning
confidence: 99%